"–How can we avoid it– We are functionaries of mankind". The philosophical testament of Edmund Husserl (2014)
In 1936, in his last work, Crisis, Husserl states that philosophy has an orientating role within culture. The purpose of this paper is to show that the characterization of the philosopher as a "functionary of mankind" is in a close relationship with the p